Development of epitaxial AlxSc1−xN for artificially structured metal/semiconductor superlattice metamaterials (Phys. Status Solidi B 2/2015). Issue 2 (February 2015) - Saha, Bivas; Saber, Sammy; Naik, Gururaj V.; Boltasseva, Alexandra; Stach, Eric A.; Kvam, Eric P.; Sands, Timothy D.
<x xml:space="preserve">Abstract</x> Since the 1960s, researchers exploring the potential of artificially structured materials for applications in quantum electronic devices and nanophotonics have sought combinations of metals and semiconductors that could be integrated on the nanoscale to make epitaxial superlattices with atomically‐sharp interfaces. Incompatibility and mismatch in the crystal structure, lattice constant and surface energies, however, have prevented development of such material systems thus far. With a motivation to use rocksalt transition metal nitrides in building epitaxial metal/semiconductor superlattices, Saha et al. (pp. 251–259) have developed AlxSc1‐xN alloy thin film semiconductors that are stable in the rocksalt phase with high AlN mole fractions and with large critical thicknesses on TiN/MgO substrates. The AlxSc1‐xN alloys developed here have tunable lattice constants that enable design and growth of high‐quality epitaxial rocksalt metal/AlxSc1‐xN superlattices that exhibit a wide range of optical, electronic and thermal properties. This novel class of metal/semiconductor superlattice metamaterials promises to catalyze development of a new set of innovative optical, electronic and energy conversion devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>